1987
DOI: 10.1111/j.1528-1157.1987.tb03659.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of Depression in Epilepsy

Abstract: Sixty-six patients with epilepsy and depression were studied. Thirty-four had a family history of psychiatric illness; depression was the most common condition. Assessed using standardised rating scales, the severity of the depression was moderate and was endogenous in approximately 40% of patients. Attendant features were high state and trait anxiety and hostility. The EEGs of the patients and a control group were not significantly different. Patients receiving phenobarbital (PB) were more depressed, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
8

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(100 citation statements)
references
References 42 publications
6
85
1
8
Order By: Relevance
“…Guilt and shame have been shown to be intrinsically adaptive affects that, when recurring, establish a proneness to experience these affects. Proneness to shame and proneness to guilt have been shown to be important presursors of depression, a mood disorder that is widespread among adults with epilepsy (26)(27)(28). The purpose of this study was to examine the attribution of shame and guilt in the earliest stages of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Guilt and shame have been shown to be intrinsically adaptive affects that, when recurring, establish a proneness to experience these affects. Proneness to shame and proneness to guilt have been shown to be important presursors of depression, a mood disorder that is widespread among adults with epilepsy (26)(27)(28). The purpose of this study was to examine the attribution of shame and guilt in the earliest stages of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Other theory hypothesizes that a seizure activity in the non-dominant hemisphere could result in neglect of negative emotions [63]. Many controlled studies comparing seizure focus with degrees of depression found increased frequencies of depression with a focus in the left hemisphere, independent of seizure type [67][68][69][70], although other studies didn't ratify this correlation [71]. A complex interaction between several factors would be employed in this association.…”
Section: Specific Psychiatric Disorders Mood Disordersmentioning
confidence: 99%
“…For example, over 50% of epileptic patients with depression have a family history of psychiatric illness (Kanner and Nieto, 1999;Robertson et al, 1987). One advantage of the SwLo rats as a model of epilepsy and depression comorbidity is that these animals have been selectively bred for over 50 generations and are genetically homogenous (Weinshenker et al, 2005; unpublished data).…”
Section: Potential Mechanisms Underlying the Swlo Seizure Phenotypesmentioning
confidence: 99%